Assessment of induced voltages in common and differential‐mode for a PV module due to nearby lightning strikes. Issue 8 (26th March 2019) - Formisano, Alessandro; Petrarca, Carlo; Hernández, Jesus C.; Muñoz‐Rodríguez, Francisco Jose
Abstract : Nearby lightning strikes are prone to induce overvoltage transients in photovoltaic (PV) modules and in their power conditioning circuitry, which can permanently damage the PV system. Therefore, it becomes important to establish a method for accurate assessment of such transients. To this aim, the authors propose a three‐dimensional (3D) semi‐analytical numerical method to study the electromagnetic transients caused in PV modules by nearby lightning strikes. The approach bases on a semi‐analytical expression of the magnetic vector potential generated by a geometrically complex lightning channel. The proposed method is able to calculate the transient overvoltage in a PV module, both in common and differential‐mode, taking also into account capacitive and inductive couplings between the internal circuit and the PV metallic frame. Both modes are required to design the surge protective devices (SPDs) in PV power systems. Comparing to the models in literature, the proposed approach explicitly considers the complex geometry of the lightning channel. Statistical analysis allows assessing the impact of channel geometry by randomly generating a number of likely lightning paths. Results show that the lightning‐induced overvoltage in a PV module is highly dependent on factors such as distance to the lightning channel and lightning channel geometry.